Reply to Commentary: Are HIV-Infected Candidates for Participation in Risky Cure-Related Studies Otherwise Healthy? - Dubé, Karine; Sylla, Laurie; Dee, Lynda (Journal of empirical research on human research ethics, 2018)
We respond to Eyal et al.’s commentary focusing on how people living with HIV participating in HIV cure-related studies are defined. We argue that the types of participants enrolled in research cannot be dissociated from the study interventions, the types of anticipated risks, and the background standard of care. As the field of HIV cure research advances, more nuance and granularity will be needed to define research criteria and acceptable risk/benefit ratios for cure study participants, as well as specific tiered protocol designs that serve to protect various participant populations from untoward risks, especially in very early phase research with interventions known to have potentially serious toxicities. We highlight key lessons from the ACTIVATE study involving a latency-reversing agent, Panobinostat, for HIV cure study design involving “otherwise healthy volunteers”.